Test based sequecing in scorm compliant e-learning courses - Lieponienė, Jurgita; Kulvietienė, Regina (Lietuvos matematikos rinkinys, 2010)
The article analyzes the importance of assessment feedback in e-learning, analyzes test based sequencing possibilities in SCORM compliant e-learning courses. The article assesses if learning management systems such as Moodle, ATutor, and Workplace Collaboration Learning System support the SCORM 2004 sequencing specification.